Band Structure Perfection and Superconductivity in Type‐II Dirac Semimetal Ir1−xPtxTe2. Issue 35 (17th July 2018) - Fei, Fucong; Bo, Xiangyan; Wang, Pengdong; Ying, Jianghua; Li, Jian; Chen, Ke; Dai, Qing; Chen, Bo; Sun, Zhe; Zhang, Minhao; Qu, Fanming; Zhang, Yi; et al.
Abstract: The discovery of a new type‐II Dirac semimetal in Ir1− x Pt x Te2 with optimized band structure is described. Pt dopants protect the crystal structure holding the Dirac cones and tune the Fermi level close to the Dirac point. The type‐II Dirac dispersion in Ir1− x Pt x Te2 is confirmed by angle‐resolved photoemission spectroscopy and first‐principles calculations. Superconductivity is also observed and persists when the Fermi level aligns with the Dirac points. Ir1− x Pt x Te2 is an ideal platform for further studies on the exotic properties and potential applications of type‐II DSMs, and opens up a new route for the investigation of the possible topological superconductivity and Majorana physics. Abstract : A type‐II Dirac semimetal in Ir1 − x Pt x Te2 with optimized Dirac dispersions is experimentally discovered by angle‐resolved photoemission spectroscopy. The Pt dopant protects the crystal structure holding the Dirac cones and tunes the Fermi level close to the Dirac point. Combining the type‐II Dirac cone, Fermi level tunability, and superconductivity together, Ir1− x Pt x Te2 provides an ideal platform for more in‐depth research of type‐II DSMs.